Effects of Waste Marble and Glass Powders on Concrete Properties and Performance - Nassar, Nour Eldeen M.A. Abo (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Concrete, consisting primarily of cement, water and aggregates, is the most used construction material all over the world and plays an important role in the growth of infrastructure and industrial sectors. Cement manufacturing industry is one of the carbon dioxide producing sources that is caused global warming. However, using the waste materials and by-products as cement replacement materials become an attractive alternative because it helps to reduce the cost of concrete and cement manufacturing, also has numerous indirect benefits such as saving energy, reducing landfill cost and protecting the environment from possible pollution effects. Nowadays, marble dust and waste glass powders are two of the most polluting waste materials for the world environment. For this reason, in this thesis; the marble dust (MD) was examined as a partial cement replacement material with seven proportions as 0%, 10%, 20%, 30%, 40%, 50%, 60% and the glass powder (GP) was used as an additive material, 8% by cement weight, in a 0.55 water-binder ratio (w/b) concrete. Finally; experimental results indicated that MD can be used as a cement replacement material up to 10% replacement and with the use of GP both physical and mechanical properties of concrete can be improved. Keywords: Concrete, Marble dust, Glass powder, Cement replacement materials, Mechanical properties, Workability, Durability, Compressive strength, Sulphate resistance.

ÖZ: Çimento, su ve agregalardan oluşan beton; tüm dünyada en çok kullanılan yapı malzemesi olmakla birlikte altyapı ve sanayi sektörlerinin büyümesinde de önemli rol oynamaktadır. Çimento üretimi endüstrisi, karbondioksit salınımına yol açtığından, küresel ısınmaya neden olan kaynaklardan birisi olarak kabul edilmektedir. Ancak, çimento yerine atık malzemeler ve yan ürünlerinin kullanılması; başta çimento üretim sırasında açığa çıkan karbondioksit gazı olmak üzere, üretim maliyetini de düşürecek ve de ayni zamanda çevre atık malzemelerden arınmış olacaktır. Bu yüzden, günümüzde çimento yerine atık malzemeler ve yan ürünlerini kullanmak cazip bir alternatif haline gelmiştir. Günümüzde dünya için; atık mermer ve cam tozlarının, çevreyi en çok kirleten atık malzemelerden oldukları bilinmektedir. Bu nedenle, bu tezde; mermer tozu (MD); %0, %10, %20, %30, %40, %50, %60 yüzdelerinde çimento yerine, cam tozu ise (GP), çimento ağıriığının %8’i miktarında beton katkı malzemesi olarak kullanılmışlardır. Bunların etkileri; su/çimeto oranı 0.55 olan betonun bazı fiziksel ve mekanik özeliklerine olan etkileri araştırılmıştır. Sonuç olarak mermer tozunun cam tozu ile birlikte kullanılmasının dayanıma olan pozitif etkilerinin artan beton yaşı ile birlikte arttığı gözlemlenmiştir. Anahtar Kelimeler: Mermer tozu, Cam tozu, Çimento yerdeğişimi, İşlenebilirlik, Dayanıklılık, Basınç dayanımı, Sülfat direnci.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2020. Supervisor: Assoc. Prof. Dr. Tülin Akçaoğlu.
Keywords: Civil Engineering; Aggregates (Building materials)--Concrete; Aggregates (Materials)--Civil Engineering; Construction Engineering--Supplementary Cementitious Materials--Waste Glass; Concrete; Marble dust; Glass powder; Cement replacement materials; Mechanical properties; Workability; Durability; Compressive strength; Sulphate resistance